Youth unemployment and poverty in Nigeria: A threat to sustainable growth and development - Surajo, Aminu Zubairu; Karim, A.H.M Zehadul (IJSRM Publication, 2016)
The paper focuses attention on the persistent problem of unemployment and poverty among the youths, which is a serious phenomenon in Nigeria. It constitutes a problem not only for the youths themselves but to the overall social, political and economic structures of the country. By examining the condition of the youths, it indicates that there is no concrete attempt by the government to connect, organize and improve the dynamisms of its youths towards sustainable national development. Unemployed youths in the country have not only been neglected and left unattended but have been imposed by unemployment and poverty. This problem not only leads to their disempowerment but also creates a situation that influences them to involve in deviant behaviours such as crime, drug trafficking, prostitutions, internet scam, election rigging and other fraudulent activities. Youth unemployment and poverty threatened peace and national security which shows that the country needs to re-consolidate, educate, and be dedicated to youths by developing policies and programmes that address their problems. Therefore, the problems associated with youth unemployment and poverty in Nigeria include government failure to empower youths to sustain a living, high rate of crime, the rapid growth of ethnic militias and Boko Haram insurgency, youth involvement in political violence and drug trafficking. The solutions to the problem of youth unemployment and poverty in the country comprise of youth empowerment, employment creation, establishing well-articulated National youth policy, propagate moral reorientation, provide sporting and recreational services and train youths the philosophy of tolerance and hardworking.